Growth and Characterisation of Nanocarbon Structures - MCEVOY, NIALL (Trinity College Dublin, 2010)
Nanocarbon materials have come to the forefront of research in recent years due to their outstanding properties and wide potential applications. Production of these materials by chemical vapour deposition (CVD) is preferable as it is scalable and compatible with existing semiconductor processing techniques. The work presented concerns the growth of carbon nanotubes, pyrolytic carbon (PyC) and graphene by thermal CVD. The growth of vertically aligned multiwall nanotube (MWNT) forests on conducting substrates (Tantalum) has been demonstrated. This is crucial for applications such as supercapacitors, vias and field emission devices where an electrical contact is needed. The lengths and purity of these MWNTs were tuned by varying the reaction temperature and pressure. Samples produced were characterised using a combination of scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Raman spectroscopy. Atomic force microscopy (AFM) analysis of annealed catalyst samples showed an increase in particle size with rising temperature. At temperatures greater than 750 oC the catalyst became non-uniform. Four different catalyst systems were investigated and a Co90Fe10 alloy was shown to give the highest purity growth. The use of a conductive carbon layer in place of Ta was also investigated. The structures grown on this catalyst system showed poor alignment and a broad diameter distribution. The growth of single wall nanotubes (SWNTs) was performed using thinner catalyst films on Al2O3 layers. Through modification of the gas flow parameters these could be grown as films or aligned forests using the same catalyst material and thickness. High purity SWNTs with diameter distributions lower than those typically seen for commercially available materials were produced. A process has been developed for the production of conducting thin films of pyrolytic carbon (PyC) on SiO2 substrates by CVD. The CVD process developed allowed for fine tuning of the film thickness grown by varying the growth temperature and dwell time used. Films had resisitivities of ~ 2 x 10-5 m and a conductivity ratio (_DC/_op) in the range 0.8 1.1. Characterisation using Raman spectroscopy and x-ray photoelectron spectroscopy (XPS) highlighted the nanocrystalline nature of films grown. Improved graphitic ordering of PyC films was achieved using a Ni catalyst and annealing treatments. Raman spectroscopy indicated the removal of amorphous carbon and an increase in crystallite size. XPS analysis indicated a removal of functional groups and improved graphitic order. Further, graphene films were grown by catalytic CVD on Ni substrates. The use of a remote O2 plasma for the functionalisation and etching of different CVD grown nanocarbons has been demonstrated. Back-etching (recess) is an important component for the integration of carbon structures in silicon technology. In the case of MWNTs forests this can be used for the introduction of controlled defect levels and under certain conditions unzips the MWNTs producing graphitic sheets. Plasma treatment of PyC films has been shown to introduce oxygenated functionalities to the surface of the films giving them enhanced electrochemical activity. Graphene films grown by catalytic CVD on Ni substrates were also subjected to plasma treatment. Raman analysis indicated a significant increase in the defect levels of graphene post etching and Raman mapping demonstrated that these defects were not confined to edges.
PUBLISHED
Keywords: Nanocarbon Materials; Nanoscience & Materials